2006
DOI: 10.1111/j.1467-7652.2006.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

An in‐built proteinase inhibitor system for the protection of recombinant proteins recovered from transgenic plants

Abstract: SummaryProteolytic degradation represents a significant barrier to the efficient production of several recombinant proteins in plants, both in vivo during their expression and in vitro during their recovery from source tissues. Here, we describe a strategy to protect recombinant proteins during the recovery process, based on the coexpression of a heterologous proteinase inhibitor acting as a 'mouse trap' against the host proteases during extraction. After

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 59 publications
1
64
0
1
Order By: Relevance
“…Furthermore, we have also found in a previous study that the ectopic expression of OC-I in the cytosol of OC-I plants increases the total protein content of tobacco leaves by 40% [45]. Such higher protein content has also been found for transgenic potato leaves expressing a tomato cathepsin D inhibitor in the cytosol [38]. However, the exact reason for this higher protein production when an inhibitor is expressed is still unclear.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Furthermore, we have also found in a previous study that the ectopic expression of OC-I in the cytosol of OC-I plants increases the total protein content of tobacco leaves by 40% [45]. Such higher protein content has also been found for transgenic potato leaves expressing a tomato cathepsin D inhibitor in the cytosol [38]. However, the exact reason for this higher protein production when an inhibitor is expressed is still unclear.…”
Section: Resultssupporting
confidence: 76%
“…Both inhibitors provided protection during the protein recovery process. Cathepsin D inhibitor expression in the cytosol further increased total soluble protein amount in transgenic potato [38].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Komarnytsky et al (2006) further confirmed that co-secretion of soybean Bowman-Birk Ser protease inhibitor reduced degradation of the immunoglobulin complexes in the secretion pathway of transgenic tobacco roots and increased antibody production. Rivard et al (2006) also found that transgenic potato expressing either tomato cathepsin D inhibitor (CDI) or bovine aprotinin showed decreased levels of cathepsin D-like and ribulose 1,5-bisphosphate carboxylase/ oxygenase hydrolysing activities in vitro, and the decreased turnover rates of the selection marker protein neomycin phosphotransferase II (NPT II). More recently, Kim et al (2007) used overlap PCR to synthesis a serine protease inhibitor sPI-II harboring the chymotrypsin and trypsin inhibitor domains in an effort to reduce proteinase activity in rice cell suspension culture and then introduced the sPI-II gene into rice cells, resulting in approximately a 77% reduction of proteinase activity in transformed cell suspension culture when compared to non-transformed culture.…”
Section: Co-expression Of Proteinase Inhibitors In Plant Bioreactorsmentioning
confidence: 98%
“…Even though various successful expression systems have been reported in plant bioreactors including the use of seed protein storage vacuoles or oil-bodies, cell suspension cultures, root exudates and chloroplasts (Borisjuk et al, 1999;Conrad and Fiedler, 1998;Downing et al, 2006;Giddings et al, 2000;Komarnytsky et al, 2000;van Rooijen and Moloney, 1995), a critical problem in plant bioreactors thus far is the low yield of the recombinant proteins due to the degradation system in plants. As a result, one of the possible solution or improvement is to co-express the target protein together with protease inhibitor to protect the protein from being degradation and thus leading to high yield of the recombinant proteins in transgenic plants (Kim et al, 2007;Komarnytsky et al, 2006;Rivard et al, 2006;Xu et al, 2004). Figure 1 shows several representative plant organelles for protein compartmentation of pharmaceuticals and their targeting or delivery strategies in plant bioreactors, where Golgi-bypassing of recombinant proteins to reach seed protein storage vacuole (PSV) would avoid unwanted plant-specific complex glycan modification.…”
Section: Introductionmentioning
confidence: 99%